Crystal structure of (μ2-1-(4,4′-bipyridine-κ2N:N′)-bis[diaqua-(4-iodopyridine-2,6-dicarboxylato-κ3O,N,O′)–cobalt(II)], C24H20Co2I2N4O12 - Hong Dong-Feng; Ye Jia-Qi; Guo Wen-Bo (Zeitschrift für Kristallographie - New Crystal Structures)
C24H20Co2I2N4O12, monoclinic, P21/c (no. 14), a = 10.5649(3) Å, b = 18.6071(6) Å, c = 7.4403(2) Å, β = 92.388(2)°, Z = 4, V = 1461.36(7) Å3, Rgt(F) = 0.032, wRref(F2) = 0.078, T = 293 K.